Effectiveness of Diaphragmatic Breathing Exercises in Enhancing Pulmonary Recovery and Expediting Water Seal Drainage (WSD) Removal in Pleural Effusion Patients at Persahabatan Hospital - Sumedi, Sumedi; Rayasari, Fitria; Santosa, Puji Raharja (STIKep PPNI Jawa Barat, 2025)
Aims: Pleural effusion, characterized by the abnormal accumulation of pleural fluid, poses significant health risks and often necessitates interventions such as water seal drainage (WSD) placement. Diaphragmatic breathing exercises (DBE) are non-invasive techniques that may enhance pulmonary recovery and expedite WSD removal by optimizing respiratory mechanics. Despite the potential benefits, limited research has explored their effectiveness in patients with pleural effusion. Objective: This study aimed to evaluate the effectiveness of diaphragmatic breathing exercises in enhancing pulmonary recovery and expediting WSD removal in pleural effusion patients at Persahabatan Hospital, Jakarta, Indonesia. Methods: A quasi-experimental, single-group pretest-posttest design was employed. Seventeen adult patients diagnosed with pleural effusion undergoing WSD placement were recruited through purposive sampling. Participants performed DBE twice daily for 15 minutes over seven days. Pulmonary recovery and WSD outcomes were assessed using a validated Pulmonary Recovery Assessment Questionnaire. Data were analyzed using paired t-tests, with statistical significance set at p < 0.05. Results: The mean age of participants was 51.71 years (±10.12), with 64.7% female. Peak current respiration significantly improved from 103.53 L/min (±36.22) pre-intervention to 165.52 L/min (±75.28) post-intervention (p = 0.000). DBE also reduced the duration of WSD placement, indicating enhanced pulmonary recovery. Participants reported high feasibility and acceptability of the intervention. Conclusion: Diaphragmatic breathing exercises significantly improve pulmonary recovery and expedite WSD removal in pleural effusion patients. These findings highlight the potential of DBE as a cost-effective, non-invasive adjunct in respiratory rehabilitation. Further research with larger sample sizes and long-term follow-up is recommended to validate these results.